The Surakarta Model: Implementing Knowledge-Based Economy Principles in Culturally Rich Medium-Sized Cities - Afrizal Fajri; Muhammad Yamin (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2025)
This study explores the implementation of Knowledge-Based Economy (KBE) principles in medium-sized cities within emerging economies, with a specific focus on Surakarta, Indonesia. While scholarly attention has primarily concentrated on major metropolitan areas in developed nations, this research addresses the significant gap in understanding how medium-sized urban centers with rich cultural heritage can successfully transition toward knowledge-based development models. Through a qualitative methodological approach using document analysis, this study examines Surakarta's strategic initiatives to integrate cultural assets with technological innovation and human capital development. The findings reveal that Surakarta has achieved notable success in establishing a